A Systematic Review of Waterborne Protozoan Pathogens in South Asia: Cases of Human Infections - Padua, Mark F F E.; Milanez, Giovanni De Jesus (Asian Journal of Biological and Life Sciences)
Aim/Background: Waterborne protozoan parasites, which include Giardia, Cryptosporidium, and Entamoeba, are considered important intestinal parasites around the world due to their high rates of morbidity and mortality. It aims to provide a clinical picture of the current status of infection of WBPP in humans in South Asian countries through documented cases. Materials and Methods: Epidemiological studies that focus on the isolation and identification of cases caused by waterborne protozoans between 2010 to 2020 in South Asia were searched systematically in PubMed and Google Scholar databases to provide an updated prevalence on the current status of the prevalence of waterborne protozoan infections in humans in South Asia. Results: A total of 19, 718 articles in PubMed and Google Scholar databases provide an updated prevalence on the current status of the prevalence of waterborne protozoan infections in humans in South Asia. 92 articles are considered in this study coming from 6 South Asian countries. Conclusion: Establishing the prevalence of waterborne protozoan pathogen infection is considered an important tool in public health mitigation programs and setting up health intervention protocols to prevent future infections. Also, the existence of surveillance studies for these waterborne protozoan pathogens is an important step in assessingthe health of the population as a whole.
Keywords: Cryptosporidium spp.; Entamoeba histolytica; Giardia spp.; South Asia; WBPP.